2005
DOI: 10.1152/ajpendo.00312.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of steroid aldoketoreductases 1C in omental adipose tissue are positive correlates of adiposity in women

Abstract: -The, and André Tchernof. Expression and activity of steroid aldoketoreductases 1C in omental adipose tissue are positive correlates of adiposity in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 40 publications
7
37
0
Order By: Relevance
“…Induction of fat cell differentiation led to a significant increase in the production of 20␣-reduced progesterone but not other metabolites (28). Moreover, we have shown that 20␣-reductase activity and expression of AKR1C isoforms in omental adipose tissue are positively associated with visceral fat accumulation (2). In the present study, we confirm that progesterone inactivation through 20␣-HSD activity is mediated mainly by AKR1C1.…”
Section: Discussionsupporting
confidence: 82%
“…Induction of fat cell differentiation led to a significant increase in the production of 20␣-reduced progesterone but not other metabolites (28). Moreover, we have shown that 20␣-reductase activity and expression of AKR1C isoforms in omental adipose tissue are positively associated with visceral fat accumulation (2). In the present study, we confirm that progesterone inactivation through 20␣-HSD activity is mediated mainly by AKR1C1.…”
Section: Discussionsupporting
confidence: 82%
“…We have observed correlations between AKR1C2 protein level in adipose tissue and parameters of adiposity ). It has also been reported that the level of AKR1C2 mRNA expression in adipose tissue of women positively correlates with adiposity (Blouin et al 2005). Similarly, Wake et al (2007) showed that central fat distribution, measured by waist/hip ratio, was associated with mRNA expression for AKR1C2 in white adipose tissue.…”
Section: Introductionmentioning
confidence: 79%
“…AKR1C activity and messenger RNA (mRNA) have also been detected in subcutaneous and OM adipose tissue in women, and OM AKR1C of progesterone is highest in women with visceral obesity. Significant positive correlations are also found between OM AKR1C activity and OM adipocyte diameter and OM adipose tissue lipoprotein lipase activity (Blouin et al, 2005 The aldosterone-regulated sodium reabsorption pathway shows enrichment with the insulin receptor (INSR), insulin receptor substrate 2 (IRS-2), and phosphatidylinositol 3-kinase (PI3K) R1 genes. Muscle-specific INSR knockout mice (fat-specific disruption of the INSR gene) exhibit a muscle-specific reduction in receptor content and early signaling events (Bruning et al, 1998).…”
Section: Discussionmentioning
confidence: 98%